Climbing behavior of Cordylancistrus sp. in the Colombian Andes - Maldonado Ocampo, Javier Alejandro; Pontificia Universidad Javeriana (2015)
The climbing behavior in a suckermouth Loricariidae catfish species is reported for the first time. A group of eight specimens of Cordylancistrus sp. were observed in situ climbing a waterfall in a mountain stream of the Colombian Andes. Here, we described how this species overcame the vertical barrier, and finally discuss and hypothesized how "key innovations" developed could play an important role in the occupation of a new niche and in the diversification of the family Loricariidae.